2021
DOI: 10.3390/bs11120164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Esteem on Self-Viewing: An Eye-Tracking Investigation on Mirror Gazing

Abstract: While some people enjoy looking at their faces in the mirror, others experience emotional distress. Despite these individual differences concerning self-viewing in the mirror, systematic investigations on this topic have not been conducted so far. The present eye-tracking study examined whether personality traits (self-esteem, narcissism propensity, self-disgust) are associated with gaze behavior (gaze duration, fixation count) during free mirror viewing of one’s face. Sixty-eight adults (mean age = 23.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The authors showed that, compared to typical subjects, subjects with high scores of narcissism have greater activation in areas of the brain which are typically correlated with expectancy violation and negative emotion. Another study (Potthoff and Schienle, 2021) performed with eye-tracking show that subjects with low self-esteem look longer at their own face, possibly reflecting a higher critical gaze on oneself. Further studies have found correlations between affective selfknowledge and psychological and behavioral responses during perception of one's own face and body.…”
Section: Feeling Toward the Mirror Imagementioning
confidence: 98%
“…The authors showed that, compared to typical subjects, subjects with high scores of narcissism have greater activation in areas of the brain which are typically correlated with expectancy violation and negative emotion. Another study (Potthoff and Schienle, 2021) performed with eye-tracking show that subjects with low self-esteem look longer at their own face, possibly reflecting a higher critical gaze on oneself. Further studies have found correlations between affective selfknowledge and psychological and behavioral responses during perception of one's own face and body.…”
Section: Feeling Toward the Mirror Imagementioning
confidence: 98%
“…These studies address theoretical and practical advances on personality in different populations and age groups, as well as the research findings of interventions and treatment strategies involving personality. Of the seven original research articles and one scoping review on personality included in this Special Issue, three are focused on healthy adult populations [ 1 , 2 , 3 ], two in healthy children and adolescent [ 4 , 5 ], other two in chronic pain conditions (migraine [ 6 ] and fibromyalgia [ 7 ]) and one in personality disorders (cluster B and C [ 8 ]). The variety of conditions, populations, personality traits and research methods used in the included studies makes difficult a direct comparison of the findings but provide a wider approach to personality, intervention, and psychological treatment.…”
mentioning
confidence: 99%
“…First, the study by Pottof et al [ 1 ] aimed at examining—for the first time—the influence of personality in the self-viewing on a mirror and others viewing on a video using different gaze parameters (duration and fixation) and the eye-tracking technique. Gender differences in gaze parameters were also analyzed.…”
mentioning
confidence: 99%
See 2 more Smart Citations